The Application of Unity-Oriented Persuasive Communication of Prophet Muhammad SAW in the Plural Society of Medina City - Nasor, M. (Jurnal Ilmiah Peuradeun, 2018)
Plural society built by the prophet was a reflection of an ideal society that can live together as the result of the application of a persuasive communication. A plural society is a society that is composed of various groups, races, tribes, nations, and others. Their existence should get a proper guidance so that people could possess certain qualities such as loving the good deeds and against the bad deeds and violence as Islam instructs. Universal Islamic values govern relations based on mutual respect, non-coercion, justice, humanity, togetherness, and brotherhood. Islam as a social religion strongly supports the effort to establish the relationship of human dignity as a whole. For that, it seems necessary to have a persuasive communication that can touch the psychological aspects of various societies. This method will be easier to bring about an effective result that is the commitment of each group on faith and humanity with the boundaries of rights and obligations. Such situation can foster motivation and confidence to achieve unity and the welfare of the people, which in turn they can live in tolerance, justice, togetherness, brotherhood, and many others.